SUBSTANTIATION OF APPLICATION OF THE STRATEGIC PLANNING METHODS IN ORDER TO IMPROVE EFFICIENCY OF THE AUTOMATED SYSTEMS OF FIRE AND EXPLOSION PROTECTION AT THE FUEL AND ENERGY COMPLEX FACILITIES IN THE SPECIAL CONDITIONS - Samarin, Ilya V.; Grinyaev, Sergey N.; Strogonov, Andrey Yu.; Topolskiy, Nikolay G.; Kruchkov, Aleksey V. (Journal of Applied Engineering Science, 2021)
This paper presents substantiation of the obligatory application of the strategic planning methods in order to improve efficiency of the automated systems of fire and explosion protection (ASFEP) at the facilities of the fuel and energy complex (FEC) in the special conditions. To this end, the technological production process of the FEC facilities is divided into destructive and creative subprocesses. It is assumed that the events that cause the potentially dangerous situations, which are connected with fires and explosions, form the destructive subprocess. The activities, which are carried out within the framework of fire safety plans at the FEC facilities and which are controlled by the shift on duty, form the creative subprocess. Events of the first subprocess reduce efficiency of the ASFEP, while events of the second subprocess increase efficiency of this system. Authors of the article propose the continuous curve of recovery of the ASFEP efficiency in order to ensure modelling the type of influence of various rehabilitation measures. Two kinds of the exponential functions enveloping the moments of fire and rehabilitation are analysed for these subprocesses. The article describes the graph of actual rehabilitation of the ASFEP efficiency taking into account assumptions concerning nature of these functions. The total efficiency of the rehabilitation measures within the creative subprocess consists of the partial efficiencies of the measures, which are included to individual plans of various subsystems of the ASFEP (subsystems of the first and second levels). These partial shares of efficiency have been analysed from the point of view of their dependency on the period of performance of these measures, on their funding and management. It was established that management of the relevant measures, which is determined with the help of the strategic planning methods, is the most significant parameter in this model.